Strategi Pengelolaan Sumber Daya Insani dalam Meningkatkan Industri Fesyen Halal - Ubaidillah, Ahmad; Ulum, Khozainul (JES (Jurnal Ekonomi Syariah), 2024)
This article aims to offer management strategy of Islamic Human Resources (IHR) in the Islamic fashion industry environment. This research is library research, with data collection techniques using books, journals, and other publications. This study uses a qualitative approach that produces descriptive data in the form of words about IHR management in the Islamic fashion industry. The collected data are then analyzed, interpreted, and generalized. The results of the study indicate that IHR development not only emphasizes intellectual and emotional development, but also involves spiritual and moral development. The presence of a truly Islamic IHR can reduce or eliminate the risk of sharia compliance in the Islamic fashion industry environment. The operationalization of IHR Islamization can be carried out through several stages, namely sharia recruitment and sharia selection. Sharia selection tools that can be used include sharia curriculum vitae (CV) analysis, sharia test, sharia interview, sharia recommendation and sharia psychological test. Everyone who works in the Islamic fashion industry needs to be Islamized through the stages of sharia recruitment and selection. It is hoped that the IHR development stages will give birth to tazkiyah or inner purification which will color all activities in the Islamic fashion industry.